Acute Drug Effects on the Human Placental Tissue: The Development of a Placental Murine Xenograft Model. (December 2018) - Verheecke, Magali; Hermans, Els; Tuyaerts, Sandra; Souche, Erika; Van Bree, Rita; Verbist, Godelieve; Everaert, Tina; Cortès-Calabuig, Alvaro; Van Houdt, Jeroen; Van Calsteren, Kristel; Amant, Frederic
Objective: A pilot study was conducted to establish a human placental xenograft, which could serve as a model to evaluate the effect of toxic exposures during pregnancy. Study Design: The protocol consisted of engraftment of third-trimester human placental tissue in immunocompromised mice, after induction of a pseudo-pregnancy state by ovariectomy and progesterone supplementation. To validate the model, the placental tissue before and after engraftment was examined by immunohistochemistry, fluorescence-activated cell sorting (FACS), single-nucleotide polymorphism (SNP) genotyping, and whole transcriptome sequencing (WTSS). The human chorion gonadotropin (hCG) production in serum and urine was examined by enzyme-linked immunosorbent assay. Results: Microscopic evaluation of the placental tissue before and after engraftment revealed a stable morphology and preserved histological structure of the human tissue. Viable trophoblast was present after engraftment and remained stable over time. Vascularization and hormonal secretion (hCG) were present till 3 weeks after engraftment. Thirty-one SNPs were equally present, and there was a stable expression level for 56 451 genes evaluated by whole transcriptome sequencing. Conclusion: Although this human placental xenograft model cannot copy the unique uterine environment in which the placenta develops and interacts between the mother and the fetus, it could be a suitable tool to evaluate the acute impact and adaptive processes of the placental tissue to environmental changes.